Pengaruh latihan circuit traning daya tahan untuk meningkatkan kesegaran jasmani pemain sepakbola u-12 SSB abhiseva Bengkulu tengah: The effect of endurance circuit training exercises to improve the physical fitness of U-12 soccer players at SSB Abhiseva Bengkulu, Central Bengkulu - Xoterik Erik; Syafrial; Bogy Restu Ilahi (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
ABSTRACT Xoterik (2018) : The Effect of Endurance Circuit Training Exercises to Improve Physical Freshness of U-12 Football Players at SSB Abhiseva Bengkulu Tengah. The purpose of this study is to determine whether U-12 soccer players at SSB Abhiseva Bengkulu Tengah are more physically fit after participating in endurance circuit training.The experimental approach is the research strategy utilized in this study.Twenty people, all U-12 players from Abhiseva Central Bengkulu, participated in this study.The findings of this study can be seen, with an increase in the average score of 15.12 following treatment with the Endurance Circuit Training Training Method from the initial value of 11.00.In addition to the increase in the average value of the final test (Post-Test), the analysis of the data description reveals that in the initial test, there were no samples with a Physical Freshness Level value. As many as 3 people (15%) received a very poor classification, 16 people (80%) received a poor classification, 1 person (5%) received a moderate classification, and no players received good or excellent classifications.In the meantime, scores increased on the final test (Post-Test), with as few as three people (15 percent) falling into the "less" category, as many as fourteen people (70 percent) achieving a "moderate" classification, as few as three people (15 percent) falling into the "good" category, and no one attaining a "very good" classification.The exercises were carried out for sixteen meetings as part of the implementation of this Circuit Training Method.There are six training stations, and each student training station performs a predetermined exercise task continuously for 30 to 60 seconds before moving on to the next training station, where the training load gradually increases.in the training program beforehand.It was demonstrated that the final test, or Post-Test, that was administered following the training process was more difficult than the initial test, or Pre-Test.The fact that the Circuit Training Method significantly improves Abhiseva Bengkulu Tengah Players' physical freshness indicates that the tcount value (7.86) is greater than the ttable value (1.725).. Keywords: Endurance Circuit Training, Increase Physical Freshness